THERMOELECTRIC GENERATORS FROM NEW MATERIALS: POSSIBILITIES FOR THE OIL AND GAS INDUSTRY OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The possibilities of using thermoelectric generators (TEG) made of new materials for generating electricity from associated petroleum gas flares and their impact on the environment are considered. Thermoelectric materials created in recent years (a solid solution of silicon and germanium doped with phosphorus and iron, a Heusler compound Fe2V0.8W0.2Al, doped silicates) can provide an efficiency of at least 20%, which suggests the prospect of widespread use of TEG in various industries. Important advantage of TEG is the possibility of cascading, which makes it possible to increase the efficiency up to 40% when using new materials. At the same time, at least 2.4 billion kWh of electricity in the amount of 1.1 trillion Uzbek sums can be annually obtained in Uzbekistan from 1.5 billion m3 of associated gas.